2015
DOI: 10.1021/acs.est.5b02827
|View full text |Cite
|
Sign up to set email alerts
|

Reducing NOx Emissions for a 600 MWe Down-Fired Pulverized-Coal Utility Boiler by Applying a Novel Combustion System

Abstract: A novel combustion system was applied to a 600 MWe Foster Wheeler (FW) down-fired pulverized-coal utility boiler to solve high NOx emissions, without causing an obvious increase in the carbon content of fly ash. The unit included moving fuel-lean nozzles from the arches to the front/rear walls and rearranging staged air as well as introducing separated overfire air (SOFA). Numerical simulations were carried out under the original and novel combustion systems to evaluate the performance of combustion and NOx em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(32 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…Various studies of the optimization of SOFA to improve boiler performance have been reported in the literature based on experiments and/or computational fluid dynamics (CFD). Increasing the SOFA ratio and optimizing its detailed distribution were found to be effective in reducing NOx emission for various boiler types [6][7][8][9][10][11][12][13]. However, the change in reaction stoichiometry can also significantly alter the combustion and heat transfer characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies of the optimization of SOFA to improve boiler performance have been reported in the literature based on experiments and/or computational fluid dynamics (CFD). Increasing the SOFA ratio and optimizing its detailed distribution were found to be effective in reducing NOx emission for various boiler types [6][7][8][9][10][11][12][13]. However, the change in reaction stoichiometry can also significantly alter the combustion and heat transfer characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is found that four kinds of down‐fired boilers are all suffered from various problems in practical operations, such as late ignition, poor combustion stability, heavy slagging, poor burnout, asymmetric combustion, especially for high NO x emissions . For down‐fired boilers with split burner, various solutions were developed to deal with these problems, such as burning pulverized coals to improve ignition and combustion stability, positioning fuel‐lean coal/air flow nozzle far from the furnace central part to weaken slagging, inclining downward wall‐air jets below furnace arches to prolong coal residence times for higher burnout, and performing comprehensive combustion retrofits to reduce NO x emissions …”
Section: Introductionmentioning
confidence: 99%
“…However, the introduced down‐fired boilers tend to function poorly when burning this type of coal in China, resulting in asymmetric combustion, late ignition, severe slagging, unstable combustion, insufficient burnout (typically with the unburnt carbon in fly ash of approximately 10%) and high NO x emission levels (around 1500 mg/m 3 at 6% O 2 ). Various solutions were proposed to solve these problems, such as adjusting the burner location and furnace parameters to avoid asymmetric combustion, changing burner operation models to mitigate slagging, retrofitting the combustion configuration to enhance the ignition and burnout, and adjusting air distribution to reduce NO x emissions. The regulation of air‐staging combustion in down‐fired boilers to simultaneously achieve significant reductions in NO x emissions, stable combustion, and good burnout is challenging.…”
Section: Introductionmentioning
confidence: 99%